Consolidation In Pakistani Banking Sector - Memon, Ziaul Haque; Shaikh, Faisal A. (JISR management and social sciences & economics, 2003)
Pakistan’s banking sector has progressed rapidly in the last few years. The trend of consolidation in the industry, which began in the US and spread to Europe, Middle East, and South East Asia, has now reached the subcontinent. A process of consolidation as a viable solution has followed each crisis in the banking sector. In the aftermath of the crisis in South East Asia in 1997, when capital outflow plunged the banking sector, central banks of the states found consolidation as one of the crucial remedies. Since Pakistan was following the South East Asian model of financial liberalization, it also adopted consolidation under the supervision of the International Monetary Fund. After the collapse of Asian tigers, weak banks were asked to increase their paid up capital from PKR 500 million to PKR 1 billion. As a result, banks had to take the consolidation route. State Bank of Pakistan became powerful regulator after an amendment in 1997 Act. The following study is an attempt to find the reasons of consolidation in the banking sector of Pakistan.